(untitled) (Global Journal of Human-Social Science, 2019)
This paper examines the methodological challenges in the infusion of civic education curriculum in adult basic and post literacy education and other forms of adult learning both in-formal, nonformal and formal education. The paper sees civic education as citizenship, democratic and human right education necessary for deepening democratic in any society but argued that the content and manner of teaching and learning civic education in Nigeria cannot ensure the achievement of the avowed objectives of the subject. As placebo, and not a medicine, the civic education curriculum content and the pedagogical strategies create the false impression of enhancing citizens’ participation in Nigeria’s democratic project. Thus the paper proposed four pedagogical frameworks such as the pedagogy of human right, resistance, citizenship and peace.